2012
DOI: 10.1039/c2mb05079j
|View full text |Cite
|
Sign up to set email alerts
|

Exploring salivary proteomes in edentulous patients with type 2 diabetes

Abstract: Type 2 diabetes and tooth loss are linked both epidemiologically and pathophysiologically. We applied label-free differential protein expression analysis using multidimensional liquid chromatography/tandem mass spectrometry (2D-LC-MS/MS) to explore the proteomic profile of saliva samples collected from selected type 2 diabetic edentulous patients and non-diabetic controls. Ninety-six peptides corresponding to 52 proteins were differentially expressed between the diabetic edentulous patients and controls (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 26 publications
(54 reference statements)
2
78
0
Order By: Relevance
“…A recent study reported the salivary proteomic profile of type 2 diabetes patients. 36 The authors found that 52 proteins were differently expressed and higher levels of some diabetesrelated inflammatory biomarkers were observed in saliva of individuals with diabetes compared to controls. Other investigators have reported that among a total of 487 analysed proteins in the saliva, 65 had higher levels in type-2 diabetes subjects compared to healthy individuals.…”
Section: Diabetesmentioning
confidence: 99%
“…A recent study reported the salivary proteomic profile of type 2 diabetes patients. 36 The authors found that 52 proteins were differently expressed and higher levels of some diabetesrelated inflammatory biomarkers were observed in saliva of individuals with diabetes compared to controls. Other investigators have reported that among a total of 487 analysed proteins in the saliva, 65 had higher levels in type-2 diabetes subjects compared to healthy individuals.…”
Section: Diabetesmentioning
confidence: 99%
“…Studies were excluded if they were review articles, proteomic techniques were not used or if they did not compare T2DM with a healthy control group. Six studies involving animals only and two comparing different proteomic approaches were further excluded leaving nine primary studies (30,31,32,33,34,35,36,37,38) evaluated in this review. Further searches of the Cochrane and EMBASE databases and hand searching of the references of relevant manuscripts did not yield additional articles.…”
Section: Resultsmentioning
confidence: 99%
“…Six out of the nine studies were classified as HQ fulfilling at least ten out of the 16 criteria (30,31,33,34,35,37). The three remaining studies were classified as LQ achieving 8 or 9 out of the 16 quality (32,36,38).…”
Section: General Characteristics Of the Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6]8 Secretomes may be classified according to various criteria, such as the type of the cell or the type of the tissue producing the secretome, or the location of the secreted proteins such as extracellular but nonsystemic, intraorgan (e.g., intrahepatic) or extracellular but systemic, extraorgan (e.g., blood, saliva, urine, or lymphatic fluid). [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Depending on the type of secretome analyzed, specific information may be obtained. For example, analysis of proteins secreted by cells grown in cell culture will reflect the health and activity of those cells.…”
Section: Secretome: Definition and Classificationmentioning
confidence: 99%